Production of Chemically Modified Shear Thickening Fluids and Investigation of Their Rheological Properties - Solmaz, Murat Yavuz; Yanen, Cenk; Kıstak, Celal; Aydoğmuş, Ercan (My University, 2024)
In this study, the rheological properties of shear thickening fluid, which are generally used as single solid phase in the literature, were investigated by chemical material reinforcement. Considering that the unique shear thickening effect of STF is used in many areas such as increasing the impact resistance of fabrics and energy dissipation, this study aims to provide guidance for investigating what STFs can do with chemical bonds as well as physical bonding.Methylene diphenyl diisocyanate (MDI) was used in varying proportions for chemical reinforcement. When the rheological properties of the suspensions reinforced with MDI as a chemical additive were evaluated, the initial viscosity values increased as the MDI ratio increased, while the solidification behavior under shear was observed significantly in the sample with 2.5% MDI ratio with increasing shear ratio.
Keywords: Rheology; Shear-thickening fluid; Chemical reaction